Synthesis, molecular structure and physicochemical properties of bis(3′-azido-3′-deoxythymidin-5′-yl) carbonate - Raviolo, Mónica Ana (2010)
3′-Azido-3′-deoxythymidine (zidovudine, AZT), a synthetic analog of natural nucleoside thymidine, has been used extensively in AIDS treatments. We report here the synthesis, X-ray crystal and molecular structure, NMR, IR and Raman spectra and the thermal behavior of a novel carbonate of AZT [(AZT–O)2Cdouble bondO], prepared by the reaction of zidovudine with carbonyldiimidazole. The carbonate compound, C21H24N10O9, crystallizes in the tetragonal space group P41212 with a = b = 15.284(1), c = 21.695(1) Å, and Z = 8 molecules per unit cell. It consists of two AZT moieties of closely related conformations which are bridged by a carbonyl group to adopt a folded Z-like shape.